The sacred canopy : elements of a sociological theory of religion - Berger, Peter L. (New York : Doubleday, 1990)
Reprint. Originally published: Garden City, N.Y.: Doubleday, 1967.
Includes bibliographical references
Keywords: Religion and sociology